A Review on the Role of AFAP1-AS1 in the Pathoetiology of Cancer - Ghafouri-Fard, Soudeh; Khoshbakht, Tayybeh; Hussen, Bashdar Mahmud; Taheri, Mohammad; Mokhtari, Majid (Frontiers in Oncology, 2021)
AFAP1-AS1 is a long non-coding RNA which partakes in the pathoetiology of several cancers. The sense protein coding gene from this locus partakes in the regulation of cytophagy, cell motility, invasive characteristics of cells and metastatic ability. In addition to acting in concert with AFAP1, AFAP1-AS1 can sequester a number of cancer-related miRNAs, thus affecting activity of signaling pathways involved in cancer progression. Most of animal studies have confirmed that AFAP1-AS1 silencing can reduce tumor volume and invasive behavior of tumor cells in the xenograft models. Moreover, statistical analyses in the human subjects have shown strong correlation between expression levels of this lncRNA and clinical outcomes. In the present work, we review the impact of AFAP1-AS1 in the carcinogenesis.